PUBLIC PERCEPTION AND PARTICIPATION OF STREET DEVELOPMENT IN KENAGARIAN SUNGAI DAREH DISTRICT OF PULAU PUNJUNG SUB PROVINCE DHARMASRAYA - -, Hasniati - (STKIP PGRI Sumbar, 2014)
Street represent one of requirement in life human being, every day human being use street to aktifitas and also its its, not only brief during but long-range during, without existence of adequate and good street transportation hence human life will annoyed. That way, of course there must be strive from government and society to develop and take care of existence of street as one of transportation medium. This research aim to know Perception and Participation Society in Road-Works Of Countryside in Kenagarian Sungai Dareh District Of Pulau Punjung Sub-Province of Dharmasraya.This Type Research is qualitative with approach of facto expost. Technique data collecting use interview, Informan in this research is taken by purposive sampling namely society residing alongside walke countryside in Kenagarian Sungai Dareh District Of Island of Punjung Sub-Province of Dharmasraya.Result of research show and perception and participacion society in road-works of countrysid in Kenagarian Sungai Dareh District Of Pulau Punjung Sub-Province of Dharmasraya that is : ( 1) Perception of society very is requiring of countryside street, government and society represent main key in road-works of countryside, without existence of good cooperation government with society road-works of countryside will not walk better, candid society in road-works of countryside, society like with road-works of countryside, silent candid society of its land for the road-works of countryside, governmental give responsibility to society to watch road-works of countryside, society less is knowing of stages;steps or process before road-works of countryside. ( 2) Society participate in road-works of countryside, vouchsafing its land, follow to hold responsible success road-works of countryside, readying and join in to assist work transport sand and stone, work along with other society, having the character of is open, important understanding [of] him road-works of countryside, fulfilling governmental fomentation to watch development, and follow to attend meeting invitation which its topic about road-works of countryside.